Constitutional Design of Minimum Age for Ministerial Candidates in Indonesia - Muhammad Ihsan; Taufiqul Hadi; Nur Sari Dewi.M (CV. Creative Tugu Pena, 2026)
The 1945 Constitution of the Republic of Indonesia and Law No. 39 of 2008 on State Ministries do not explicitly set a minimum age requirement to become a minister. This omission may lead to legal uncertainty. This study aims to formulate an ideal constitutional design that aligns with the principles of the rule of law, equal rights of citizens, and the presidential system of government as mandated by the 1945 Constitution of the Republic of Indonesia. The method used in this study is normative legal research, employing a legislative, conceptual, and comparative legal approach. Primary and secondary legal materials were collected through literature studies and then analyzed qualitatively using prescriptive-analytical techniques. The results of the study indicate that setting a minimum age limit for ministerial candidates could create legal uncertainty and contradict the guarantee of equality before the law. This study concludes that an appropriate constitutional design requires an age limit that is proportional and measurable, formulated through a legislative program or judicial review of the Law on State Ministries, to ensure legal certainty while encouraging the realization of transparent governance.